2019
DOI: 10.1016/j.matchar.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of microstructure and texture evolution of a Mg/Al laminated composite elaborated by accumulative roll bonding

Abstract: The microstructure and texture of an Al1050/AZ31/Al1050 laminated composite fabricated by accumulative roll bonding at 400°C up to 5 cycles are investigated using Electron BackScatter Diffraction, neutron diffraction, microhardness measurements and tensile tests. EBSD analysis has shown that ARB processing led to microstructural refinement with equiaxed grain microstructure in AZ31 layers and to the development of elongated grains parallel to the rolling direction in Al 1050 layers. No new phases formed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The scanned areas were 80 × 80 μm 2 with a 0.2 μm step size. The grainsize data were obtained using the usual clean up procedure with grain tolerance angle of 5° and a minimum grain size set at 5 pixels [21,[49][50][51][52]. All datum points with a confidence index lower than 0.05 were excluded from the analysis; the confidence index quantifies the reliability of the indexed pattern [53].…”
Section: Microstructural and Textural Observationsmentioning
confidence: 99%
“…The scanned areas were 80 × 80 μm 2 with a 0.2 μm step size. The grainsize data were obtained using the usual clean up procedure with grain tolerance angle of 5° and a minimum grain size set at 5 pixels [21,[49][50][51][52]. All datum points with a confidence index lower than 0.05 were excluded from the analysis; the confidence index quantifies the reliability of the indexed pattern [53].…”
Section: Microstructural and Textural Observationsmentioning
confidence: 99%
“…ARB is yet another SPD method that has been given less attention in near- α Ti alloys development, despite its successful application to Al alloys (Habila et al , 2019; Morovvati and Dariani, 2017; Wang et al , 2018), steel (Etemad et al , 2019; Lin et al , 2019; Nunes and Machado, 2018), CP titanium (Fattah-alhosseini et al , 2017; Karimi et al , 2018; Karimi et al , 2016) and other alloys and composites. The process involves rolling two precursor sheets at 50 per cent reduction thickness to obtain a stack of multilayered sheets with high plastic strain and ultrafine grains.…”
Section: Development Of High Strength Near-α Titanium Alloysmentioning
confidence: 99%
“…During the ARB process, the strain gradient arises through the thickness and leads to microstructure and heterogeneous texture evolution [17]. Therefore, the anisotropy of ARBed sheets and their improved mechanical properties have their own origins in the modified textures, microstructural evolutions, and heterogeneities [17][18][19]. Since the texture of ARBed sample is distinctly different from other rolling process results, it is essential to study texture, the orientation of precipitates, and the mechanical and microstructural properties of the sheets after ARB [20].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the texture of the ARBed samples was almost the same in each ARB cycle, and the difference was only in the texture intensity [16]. Using the tensile test, electron backscatter diffraction (EBSD), and neutron diffraction, Walid Haliba et al [18] studied the texture and microstructure of Mg/Al ARBed composite. They found that refined microstructure and equiaxed grains resulted due to the ARB process.…”
Section: Introductionmentioning
confidence: 99%